Dynamic vs. Static Wholesale Pricing Strategies in a Dual-Channel Green Supply Chain - Yongzhao Wang; Xiaojie Sun (Complexity)
With the improvement of social environmental awareness, the dual-channel green product sales mode has been widely used by many manufacturing firms. In this paper, we consider a dual-channel green supply chain where one manufacturer produces a green product and sells it through one retail channel and its own direct channel. Consumers in the two channels have different perceptions of the product energy efficiency level due to different purchasing experiences. The product energy efficiency level evolves over time and is characterized as a dynamic variable. By developing and solving the Stackelberg differential game problems under the dynamic and static wholesale pricing strategies, respectively, we obtain the main results in this paper. First, the manufacturer has more incentives to invest in green innovation when more consumers buy the green product through the direct channel. Second, the manufacturer prefers to adopt the dynamic wholesale pricing strategy in most cases and prefers the static one only when the consumers in both channels have relatively high energy efficiency perceptions. By introducing the transfer payment contract, we show that the static wholesale pricing strategy may be the better choice, which leads to a win-win outcome for both members. Finally, sensitivity analysis further provides some managerial insights and verifies the robustness of the results.